Impact of Brand Origin on Consumer's Purchase Decision and Brand Loyalty: A Study on America Automotive Brand (Chevrolet) - Soraya, Farah Diba B1024151009 (Jurnal Manajemen Update, 2019)
ABSTRACTThe purpose of this study is to investigate the impact of brand origin on consumerâ€™s purchase decision and brand loyalty toward an automotive brand originated from USA, Chevrolet. In the automotive or car industry, American brands especially Chevrolet seems less attractive for Indonesia consumers base on its market share compare to Japan brands. However, the brand origin of Chevrolet might affect the Pontianak consumerâ€™s perspective and behavior to consider this brand to be one of their choices along with other car brands. This research is a survey research that is conducted to understand the causal relationships between variables with the use of questionnaire as the instrument to obtain data. The questionnaire is distributed to 100 sample who fulfill the requirements. The sample of this research is Chevrolet consumer in Pontianak with the age range between 21 - 55 years old. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using smartPLS 3.0 software. The hypothesis of the research is H1: There is a significant relationship between country image and consumerâ€™s purchase decision towards Chevrolet car, H2: There is a significant relationship between Country Image and consumerâ€™s Brand Loyalty towards Chevrolet car, H3: There is a significant relationship between Perceived Quality and consumerâ€™s Purchase Decision towards Chevrolet car, H4: There is a significant relationship between Perceived Quality and consumerâ€™s Brand Loyalty towards Chevrolet car, H5: There is a significant relationship between Brand Familiarity and consumerâ€™s Purchase Decision towards Chevrolet car, H6: There is a significant relationship between Brand Familiarity and consumerâ€™s Brand Loyalty towards Chevrolet car, and H7: There is a significant relationship between Purchase Decision and Brand Loyalty towards Chevrolet car. The result of this research shows that H2, H3, H4, and H7 are accepted but H1, H5, and H6 are rejected.Â Keyword: Brand origin, Familiarity, Loyalty, Country Image, Chevrolet, USA, Car REFERENCESAaker, D. (1996). Measuring Brand Equity Across Products and Markets. New York: Free Press.Aaker, D. A. (1991). Managing Brand Equity. New York: The Free Press.Abdolvand, F. E. (2016). The impact of country-of-origin image on brand loyalty: Evidence from Iran. Asia Pacific Journal of Marketing and Logistic.Ahmed, Z. U., Johanson, J. P., & Boon, L. C. (2004). Does country-of-origin matter for low-involvement products. International Marketing Review, 102-120.Alba, J. W., & Hutchinson, J. W. (1987). Dimensions of consumer expertise. Journal of Consumer Research, 14-25.Alba, J. W., & Mormorstein, H. (1987). The effects of frequency knowledge on consumer decision making. Journal of Consumer Research, 14-25.Allaway, A., Whipple, W. J., Huddleston, P., & Ellinger, E. A. (2011). Customer-based Brand Equity, Equity Drivers, and Customer Loyalty in Supermarket Industry. Journal of Product and Brand Management, 190-204.AlSulaiti, K. I., & Baker, M. J. (1998). Country of origin effects: a literature review. Marketing Intelligence and Planning, 150-199.Armstrong, G., & Kotler, P. (2005). Marketing: An Introduction. 7th Edition. Upper Saddle River: Prentice Hall.Baeza, J., & Anmo, C. (2010). Brand Origin â€“ How Does it Impact Brand Awareness and Brand Image. Kristianstad University.Barich, H., & Kotler, P. (1991). A Framework for Marketing Image Management. Sloan Management Review, 94-104.Bayraktar, A. (2015). The effect of macro and micro country image on consumersâ€™ quality perceptions:evidence from a developed and a developing country. American Journal of Business Research, 59-73.Bhuian, S. (1997). Marketing cues and perceived quality: Perception of Saudi consumers toward products of the U.S., Japan, Germany, Italy, U.K. and France. Journal of Quality Management, 217-325.Bloemer, J., & Kasper, H. D. (1995). The complex relationship between consumer satisfaction and brand loyalty. Journal of Economic Psychology, 311-329.Brucks, M. (1985). The effects of product class knowledge on information search behavior. Journal of Consumer Research, 1-16.Bryman, A. (2012). Social research Method. Oxford University Press.Chevrolet. (2019). About Us: History & Heritage. Retrieved from Chevrolet Indonesia: https://www.chevrolet.co.id/culture/article/history-and-heritage.htmlCordell , V. V. (1992). Effects of consumer preferences for foreign sourced products. Journal of International Business Studies, 694-9.Dafler, F. (2013, April 23). Terindah. Retrieved from Memahami dan Mempelajari SmartPLS: http://feroniadafler.blogspot.co.id/2013/04/mempelajari-dan-memahami-smartpls.htmlDavis, F. D. (1989). Perceived usefulness, perceived ease of use, and user acceptance of information technology. MIS Quarterly, 319-340.Dick, A. S., & Basu, K. (1994). Customer Loyalty: Toward an Integrated Conceptual Framework. Journal of the Academy of Marketing Science, 99-113.Dodds, B. K., Monroe, K. B., & Grewal, D. (1991). Effect of Price, Brands and Store Information on Buyersâ€™ Product Evaluation . Journal of Marketing Research, 307-319.Eagly, A. H., & Chaiken, S. (1993). The psychology of attitudes. Fort Worth, TX: Harcourt Brace Jovanovich.Eng, T. Y., Ozdemir, S., & Michelson , G. (2016). Brand origin and country of production congruity evidence from the UK and China. Journal of Business Research, 5703-5711.Engracia Giraldi, J. D., Engracia Giraldi, I. D., & Scaduto, A. A. (2011). Brazils image as a social representation process. African Journal of Business Management, 8821-8831.Erfan Severi, K. C. (2013). The Mediating Effects of Brand Association, Brand Loyalty, Brand Image and Perceived Quality on Brand Equity. Asian Social Science.Erickson, G. M., Johansson, J. K., & Chao, P. (1984). Image variables in multi-attribute product evaluations: country-of-origin effects. Journal of Consumer Research, 694-699.Fishbein, M., & Ajzen, I. (1975). Belief, Attitude, Intention, and Behavior: An Introduction to Theory and Research. Addison-Wesley, Reading, MA, 129-385.Gaikindo. (2019, March 12). Indonesian Automobile Industry Data. Retrieved from GAIKINDO: https://www.gaikindo.or.idGall, M. D., Gall, J. P., & Borg, W. R. (2007). Educational research: An introduction (8th ed.). Boston:MA: Pearson Education, Inc.Gao, H. Z., & Knight, J. (2007). Pioneering advantage and product-country image: evidence from an exploratory study in China. Journal of Marketing Management, 367-385.Garvin, D. A. (1984). What Does Product Quality Really Mean. Sloan Management Review, 25-43.Ghozali, I. (2008). Structural Equation Modelling, Edisi II. Semarang: Universitas Diponegoro.GonzÃ¡lez, M., ComesaÃ±a, L., & Brea, J. (2007). Assessing tourist behavioral intentions through perceived service quality and customer satisfaction. Journal of Business Research, 153-160.Gurhan-Canli, Z., & Maheswaran, D. (2002). Determinants of country-of-origin evaluations. Journal of Consumer Research, 96-108.Ha, H., Janda, S., & Park, S. (2009). Role of satisfaction in an integrative model of brand loyalty: evidence from China and South Korea. International Marketing Reviews, 198-220.Han, C. M. (1989). Country image: halo or summary construct? Journal of Marketing Research, 222-229.Han, G., & Wang, X. (2012). Understanding â€˜made in Chinaâ€™: valence framing and product-country image. Journalism & Mass Communication Quarterly, 225-243.Hanzee, K. H., & Khosrozadeh, S. (2011). The Effect of the Country-of-Origin Image, Product Knowledge and Product Involvement on Information Search and Purchase Intention. Middle-East Journal of Scientific Research, 625-636.Harshini, C. S. (2015). Influence of Social Media Ads on Consumerâ€™s Purchase Intention. International Journal of Current Engineering and Scientific Research (IJCESR).Heffner, C. L. (2016). Test Validity and Reliability. Retrieved from AllPsych: http://allpsych.com/researchmethods/validityreliability/Heimbach, A. E., Johannson, J. K., & Maclachlan, D. L. (1989). Product familiarity, information processing, and country-of-origin cues. NA-Advances in Consumer Research, 460-467.Henry. (2011, August 24). Path Analysis with LISREL (Chapter 1). Retrieved from Teori Online: https://teorionline.wordpress.com/2011/08/24/path-analysis-with-lisrel-chapter-1/Hong, S. T., Robert, S., & Wyer, R. J. (1990). Determinants of product evaluation: effects of the time interval between knowledge of a productâ€™s country-of-origin and information about its speciï¬c attributes. Journal of Consumer Research, 277-288.Hox, J. J., & Bechger, T. (2011). An Introduction to Structural Equation Modeling. Family Science Review, 354-373.Hsieh, M. H. (2004). An Investigation of Country-of-origin effect using Correspondence Analysis, A Cross-national Context. International Journal of Marketing Research, 267-295.Hsu, C. H., Oh, H., & Assaf, A. G. (2011). A customer-based brand equity model for upscale hotels. Journal of Travel Research, 81-93.Jabareen, Y. (2009). Building Conceptual Framweork: Philosophy, Definitions, and Procedure. International Journal of Qualitative Methods.Javed, A., & Hasnu, S. F. (2013). Impact of Country-of-Origin on Product Purchase Decision. Journal of Marketing and Consumer Research, 31-51.Jin, B., & Yong, G. (2005). Integrating effect of consumer perception factors in predicting private brand purchase in a Korean discount store context. Journal of Consumer Marketing, 62-71.Jin, Z., Chansarkar, B., & Kondap, N. M. (2006). Brand origin in an emerging market: perception of Indian consumers. Asia Pacific Journal of Marketing and Logistics, 283-302.Jin, Z., Chansarkar, B., & Kondap, N. M. (2006). Brand origin in an emerging market: perceptions of Indian consumers. Asia Pacific Journal of Marketing and Logistics, 283-302.Johannson, J. K. (1989). Determinants and effects of the use of `made in' labels. International Marketing Review, 47-58.Johansson, J. K., Douglas, S. P., & Nonaka, I. (1985). Assessing the impact of country-of-origin on product evaluations: a new methodological perspective. Journal of Marketing Research, 96.JoYang, Lim, D., & Choi, H. (2011). An empirical study on the Chinese consumersâ€™ global brand preference and purchase. Journal of International Trade and Industry Studies, 79-114.Karahanna, E., Straub, D., & Chervany, N. (1999). Information Technology Across Time: A Cross-Sectional Comparison of Pre-Adoption and Post-Adoption Belief. MIS Quarterly, 183-214.Keller, K. (2008). Strategic Brand Management. Pearson.Kocuglu, K., Tengilimoglu, D., Ekiyor, A., & Guzel, A. (2015). The Effects of Brand Loyalty on the Consumer Buying Behaviors: The Example of Perfume in the Province of Ankara. International Journal of Humanities and Management Sciences .Koschate-Fischer, N., Diamantopoulos, A., & Oldennkotte, K. (2012). Are Consumers Really Willing to Pay more for Favorable Country Image? A study of Country-of-Origin Effects on Willingness to Pay. Journal of International Marketing , 19-41.Kothari, C. (1985). Research Methodology-Methods and Techniques. New Delhi: Wiley Eastern Limited.Kotler, P., & Armstrong, G. (2012). Principles of Marketing. England: Prentice hall.Kotler, P., & Gertner, D. (2002). Country as brand, product, and beyond: a place marketing and brand management perspective. Journal of Brand Management, 249-261.Laroche, M., Papadopoulos , N., Heslop, A., & Mourali, M. (2005). The influence of country image structure on consumer evaluation of foreign products. International Marketing Reviews, 96-115.Lee, C. W., Suh, Y. G., & Moon, B. J. (2001). Product-country images: the roles of country-of-origin and country-of-targeting. Journal of International Consumer Marketing, 47-62.Lee, S., & Li, M. (2011). A study on the effects of product-country image, corporate image and brand equity and purchase intention of Chinese youth: focused on the cell phones of three countries brands. Korea Research Academy of Distribution and Management Review, 167-191.Lew, S., & Sulaiman, Z. (2013). Consumer Purchase Intention towards Products Made in Malaysia vs. Made in China: A Conceptual Paper. Procedia-Social Behavioral Sciences 130, 37-45.Li, G., Park, E. M., & Park, S. T. (2016). Effects of social media usage on country image and purchase intention from social p2p network perspective. Peer-to-Peer Networking & Applications, 487-497.Li, W. K., & Wyer, R. J. (1994). The role of country-of-origin in product evaluations: informational and standard-of-comparison effects. Journal of Consumer Psychology, 187-212.Lin, L. Y., & Chen, C. S. (2006). The inï¬‚uence of the country-of-origin image, product knowledge and product involvement on consumer purchase decisions: an empirical study of insurance and catering services in Taiwan. Journal of Consumer Marketing, 248-265.Lin, Y. C. (2012). Evaluation of Co-branded Hotel in the Taiwanese Market: The Role of Brand Familiarity and Brand Fit. Journal of Contemporary Hospitality Management, 346-364.Liputan 6. (2017, September 19). Otomotif: 10 Merek Eropa dan Amerika di Indonesia, Siapa Terlaris? Retrieved from Liputan 6: https://www.liputan6.com/otomotif/read/3099835/10-merek-eropa-dan-amerika-di-indonesia-siapa-terlarisMackenzie, S. B., & Lutz, R. J. (1989). An Empirical Examination of the Structural Antecedents of Attitude toward the Ad in an Advertising Pretesting Context. Journal of Marketing, 48-65.Magnusson, P., Westjohn, S. A., & Zdravkovic, S. (2011). What? I thought Samsung was Japanese: accurate or not, perceived country of origin matters. International Marketing Review, 454-472.Maheswaran, D. (1994). Country-of-origin as a stereotype: effects of consumer expertise and attribute strength on product evaluations. Journal of Consumer Research, 354-365.Martin, I. M., & Eroglu, S. (1993). Measuring a Multidimensional Construct: Country Image. Business Res., 191-210.McConnell, J. (1968). The development of brand loyalty: an experimental study. Journal of Marketing Research, 13-19.Nelwan, J., Pangemanan, S. S., & Tielung, M. J. (2016). The Influence of Brand Image, Perceived Quality and Country of Origin Toward Consumer Purchase Decision of Smartphone Product in Manado. Jurnal Berkala Ilmiah Efisiensi, 168-176.Oliver, R. (1999). Whence Consumer Loyalty. Journal of Marketing.Papadopoulos , N., & Heslop, L. A. (1993). Product-Country Images: Impact and Role in International Marketing. International Business Press, Binghamton, New York, NY.Pappu, R., Quester, P. G., & Cooksey, R. W. (2006). Consumer-based brand equity and country-of-origin relationships: some empirical evidence. European Journal of Marketing, 696-717.Pappu, R., Quester, P. G., & Cooksey, R. W. (2007). Country Image and Consumer-based Brand Equity: Relationships and Implications for International Marketing. Journal of International Business Studies, 726-745.Parkvithee, N., & Miranda, M. J. (2012). . The Interaction Effect of Country-of-origin, Brand equity and purchase involvement on Consumer Purchase Intentions of Clothing Labels. Asia Pacific Journal of Marketing and Logistics, 7-22.Rao, A. R., & Monroe, K. B. (1988). The moderating effect of prior knowledge on cue tilization in product evaluations. Journal of Consumer Research, 253-264.Rashid, A. B., Ali Shah, S. M., Farooq, M. U., & Anwar, M. (2018). mpact of Brand Origin on Brand Loyalty: A Case of Personal Care Products in Pakistan. International Journal of Economics and Management Engineering, 1065-1068.Rezvani, S., Dehkordi, G. J., Rahman, M. S., Fouladivandal, F., Eghtebasi, S., & Habibi, M. (2012). A Conceptual Study on the Country of Origin Effect on Consumer Purchase Intention. Asian Social Science, 205-215.Richsen, H. (2015). Validity. Retrieved from Linguistic: http://linguistics.byu.edu/faculty/henrichsenl/ResearchMethods/RM_2_18.htmlRoth, M. S., & Romeo, J. B. (1992). Matching product category and country image perceptions: a framework for managing COO effects. Journal of International Business Studies, 157-169.Saunders, M. N., Lewis, P., & Thornbill, A. (2000). Research Methods for Business Studies. FT Prentice Hall.Shi, B., Zhang, D., Xie, H. L., & Zhou, Y. (2016). Antecedents of Chinese adolescentsâ€™ purchase intention for local brands: the moderating influence of materialistic values. Journal of Consumer Marketing, 292-301.Tepeci, M. (1999). Increasing brand loyalty in the hospitality industry. International Journal of Contemporary Hospitality Management, 223-230.Thakor, M. V., & Kohli, C. S. (1996). Brand Origin: Conceptualization and Review. Journal of Consumer Marketing, 27-42.Thakor, M. V., & Lavack, A. M. (2003). Effect of perceived brand origin associations on consumer perceptions of quality. Journal of Product & Brand Management, 394-407.Thuy, T. V., & Nguyen, C. T. (2015). Factors Influencing Customer Perceived Quality and Purchase Intention toward Private Labels in the Vietnam Market: The Moderating Effects of Store Image. International Journal of Marketing Studies, 51-63.Tran, V.-D., Keng, C.-J., & Thi, T. M. (2013). Relationships among Brand Experience, Brand Personality, And Customer Experiential Value. Contemporary Management Research, 247-262.Tuominen, P. (1999). Managing Brand Equity. 65-100.Uzoagulu, A. E. (2011). Practical Guide to Wriiting Research Project Reports Intertiary Institutions. Enugu: Cheston Ltd.Van der Schaar Investments B.V. Delft The Netherlands. (2018, April 2). Automotive Manufacturing Industry. Retrieved from Indonesia Investment: https://www.indonesia-investments.com/business/industries-sectors/automotive-industry/item6047?Vinzi, V., W. W., H., & Wang, H. (2010). Handbook of Partial Least Squares: Concepts, Methods, and Apllication. New York: Springer Publishing.Wang, X., & Yang, Z. (2008). Does country-of-origin matter in the relationship between brand personality and purchase intention in emerging economies? Evidence from Chinaâ€™s auto industry. International Marketing Review, 458-474.Wardani, P. (2012). Faktor-faktor yang Mempengaruhi Luas Pengungkapan Sukarela. Surabaya: Fakultas Bisnis Universitas Katolik Widya Mandala.Wikipedia. (2015). Convergent Validity. Retrieved from Wikipedia: https://en.wikipedia.org/wiki/Convergent_validityWikipedia. (2016). Wikipedia. Retrieved from Discriminant Validity: https://en.wikipedia.org/wiki/Discriminant_validityYasin, M. N., Noor, N. M., & Mohamad, O. (2007). Does image of country-of-origin matter to brand equity. Journal of Product & Brand Management, 38-48.Yee, C., & San, N. C. (2010). Consumersâ€™ Perceived Quality, Perceived Value and Perceived Risk Towards Purchase Decision on Automobile. American Journal of Economics and Business Administration.Yoo, B., Dhontu, N., & Lee, S. (2000). An examination of selected marketing mix elements and brand equity. Journal of the Academy of Marketing Science, 195-211.Yunus, N. N., & Rashid, W. E. (2015). The Influence of Country-of-origin on Consumer Purchase Intention: The Mobile Phones Brand from China. Procedia Economics and Finance, 343-349.Zeithaml, V. (1988). Consumer perceptions of price, quality and value: a means-end model and synthesis of evidence. Journal of Mareting, 2-22.Zeugner, K. P., & Diamantopoulus, A. (2010). Advancing the Country Image Construct. Journal of Business Research, 446-449.Zhuang, G., Wang, X., Zhou, L., & Zhou, N. (2008). Asymmetric effects of brand origin confusion: Evidence from the emerging market of China. International Marketing Review, 441-457.